Leverage and debt maturity choices by undiversified owner-managers - Fu, Richard; Subramanian, Ajay (Journal of Corporate Finance, 2011)
We examine the financing choices of undiversified owner-managers in a continuous-time model. Managers' financing choices as well as their dynamic equity stakes, which trade off their private benefits and the costs they incur due to their lack of diversification, are simultaneously and endogenously determined. Our analysis leads to the novel, empirically testable implications that leverage increases with the drift or expected growth rate of the firm's earnings. Debt maturity varies non-monotonically in a U-shaped manner with the project's drift and with its volatility. The predicted variations of leverage and debt maturity with the actual drift of earnings (controlling for the risk-neutral drift) are key implications of our theory that arise from the incorporation of agency conflicts between undiversified managers and well-diversified outside investors. They cannot, therefore, be obtained in traditional capital structure models in which all agents are well-diversified. Our predictions for the variation of leverage and debt maturity with project characteristics potentially reconcile empirical findings that are not consistent with previous theories. We also derive additional novel implications that link manager-specific characteristics – the discount rate or “degree of myopia” and the risk aversion – to leverage and debt maturity. These implications provide support for growing empirical evidence of the significant impact of manager characteristics and manager “fixed effects” on corporate financial policies.